الادارة الصفية وعلاقتها بالدافعية للتعلم لدى تلاميذ ثانوي - خته، سامية, قرميط، نبيلة (جامعة الوادي university of Eloued, 2020)
الملخص: تهدف هذه الدراسة الى الكشف عن وجود علاقة بين الادارة الصفية والدافعية للتعلم لدى تلاميذ الثانوي وذلك من خلال الاجابة على تساءول الدراسة . هل توجد علاقة بين الادارة الصفية والدافعية للتعلم لدى تلاميذ الثانوي؟. وعليه فقد وقعت الدراسة في جانبين اولا جانب نظري تم خلاله التطرق الى متغيرات الدراسة وثانيا جانب ميداني استخدمنا فيه المنهج الوصفي المناسب لهذه الدراسة وقمنا بجمع بيانات من العينة المكونة من 150 تلميذ من ثانوية غربي بشير بكوينين بحاسي خليفة بالوادي الذي يمثل مجتمع الدراسة في سنة 2019/2020. وتحصلنا على النتائج التالية : توجد علاقة ارتباطية ذات دلالة احصائية بين الادارة الصفية والدافعية للتعلم لدى تلاميذ الثانوي. RésuméM : انجلزية This studu aims to detect the limitation of a relatiochip between class room management and the motivation to learn for secondary school students by answering the studys question . Is therea correlation between classroom management and the motivation to lear for ligh school student Accordingly the sludy took place between to aspects first a theoretical on through which the study variables were addressed and scondry a field aspect in which we used the descriptive approach appropriate for this study and we collected data from a sample of 150 students from GharbiBachir secondary school in HassiKhalifa who represent the study population in the 2019/2020 academic year. We get the following results . There is a rolational relationship of statistical significant between classroom management and the motivation to learmscendry school students.
(دراسة ميدانية بثانوية غربي بشير بحاسي خليفة ب الوادي).
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الإدارة الصفية، الدافعية للتعلم; gestion de classe, motivation à apprendre; classroom management, motivation to learn